PERUBAHAN STRUKTUR PENDUDUK AKIBAT PEMBANGIUNAN INDUSTRI PARIWISATA DI PROPINSI BALI - Ida Bagoes Mantra (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1993)
Tourism industry in the Province of Bali has rapidly developed lately. This has consequently led to the increase of the number of both foreign and domestic tourist who come to visit Bali.The rapid development of tourist industry in Bali has certain impact on the existing demograpgic structure. As an example, the populatuin growth in the tourist areas has increased considerably caused by the number of migrants who came to the region. Most of these people are non-permanent migrants of which the exact number is never known. If prior to the 1970s the population were clustered in the fertile regions, the population distribution has now changed to following the distribution of tourist industry.Tourist industry may stimulate the people of the rural areas to utilize the present existing economic opportunities. Development both in phusycal an non-physycal aspect in the rural areas is followed by the improvement of transport facilities. These close relations have positively influenced the slight demographic structural difference between urban and rural.